DNA vaccine encoding human papillomavirus antigens flanked by a signal peptide and a KDEL sequence induces a potent therapeutic antitumor effect - Pérez Trujillo, José Juan; Garza Morales, Rodolfo; Barrón Cantú, José A.; Figueroa Parra, Gabriel; García García, Aracely; Rodríguez Rocha, Humberto; García Juárez, Jaime; Muñoz Maldonado, Gerardo Enrique; Saucedo Cárdenas, Odila; Montes de Oca Luna, Roberto; Loera Arias, María de Jesús (2017)
Abstract. Cellular immune responses play a critical role in the eradication of intracellular infections and malignant cells through the recognition and subsequent removal of the infection or malignant cells. Effective antigen presentation is crucial for stimulating the immune system against malignant cells. Calreticulin (CRT) has been used to improve antigen presentation. However, CRT overexpression has been previously associated with the development of pancreatic and breast cancer. The import and retention signals of CRT in the endoplasmic reticulum (ER) can be used to overcome CRT overexpression. The present study describes the potent antitumor effect of a DNA vaccine encoding human papillomavirus type 16 E6 and E7 antigens flanked by ER import and retention signals (SP-E6E7m-KDEL). The effect of this vaccine was compared with that of E6 and E7 antigens fused to human full-length CRT (hCRT-E6E7m). In the present study, the effectiveness of SP-E6E7m-KDEL for inducing an interferon-γ antigen‑specific, response and its therapeutic effect against tumors was demonstrated, which was as effective as immunization against those antigens fused to CRT. This simplified strategy, using ER import and retention signal peptides to direct antigens to this organelle, provides an efficient alternative to traditional vaccines and, more importantly, a safe and potent system to induce a therapeutic antitumor response.